Cardioneuroablation for the treatment of reflex syncope and functional bradyarrhythmias: A Scientific Statement of the European Heart Rhythm Association (EHRA) of the ESC, the Heart Rhythm Society (HRS), the Asia Pacific Heart Rhythm Society (APHRS) and the Latin American Heart Rhythm Society (LAHRS) - Aksu, Tolga; Brignole, Michele; Calo, Leonardo; Debruyne, Philippe; Di Biase, Luigi; Deharo, Jean Claude; Fanciulli, Alessandra; Fedorowski, Artur; Kulakowski, Piotr; Morillo, Carlos; Moya, Angel; Piotrowski, Roman; et al. (Europace, 2024)
Cardioneuroablation has emerged as a potential alternative to cardiac pacing in selected cases with vasovagal reflex syncope, extrinsic vagally induced sinus bradycardia-arrest or atrioventricular block. The technique was first introduced decades ago, and its use has risen over the past decade. However, as with any intervention, proper patient selection and technique are a prerequisite for a safe and effective use of cardioneuroablation therapy. This document aims to review and interpret available scientific evidence and provide a summary position on the topic.
Keywords: ablace; Consensus; Humans; Ablation Techniques; Vasovagal syncope; Atrioventricular block; Heart Rate; Syncope, Vasovagal; výsledek terapie; lidé; Autonomic nervous system; bradykardie; katetrizační ablace; konsensus; Bradycardia; srdeční frekvence; Treatment Outcome; vazovagální synkopa; Sinus bradycardia; Catheter Ablation; Reflex syncope